Bacterial cellulose/graphene oxide aerogels with enhanced dimensional and thermal stability. (15th February 2020) - Pinto, Susana C.; Gonçalves, Gil; Sandoval, Stefania; López-Periago, Ana M.; Borras, Alejandro; Domingo, Concepción; Tobias, Gerard; Duarte, Isabel; Vicente, Romeu; Marques, Paula A.A.P.
Highlights: Bacterial cellulose/graphene oxide (BC/GO) aerogels were prepared by solvent mixing. A small amount of DMSO addition during hydrogel formation allow pores orientation. BC/GO reduced with NH3 (gas-phase) show enhanced mechanical and thermal performance. The reduced BC/GO aerogels present notable values of electric conductivity. Abstract: We present a novel method for processing bacterial cellulose/graphene oxide (BC/GO) aerogels with multifunctional properties. The addition of a small amount of dimethyl sulfoxide (DMSO) to the aqueous dispersion of the nanomaterials during the gelification process affected the water freezing temperature of the system and thereby affecting the porous structure of the aerogel obtained after liophilization. The possibility to obtain small and elongated pore with axial orientation allowed a significant improvement of the structural stability of the aerogels. Moreover, the aerogels reduction by thermal treatment with ammonia gas induced crosslinking between the different nanophases, thus given an incremental factor for the mechanical performance of the aerogels under harsh conditions. The resulting aerogels also showed significant improvements in terms of thermal stability and electrical conductivity. These multifunctional BC/GO aerogels present high potential as sustainable and ecological alternative materials for lightweight packaging, filters for atmosphere and water treatment, or energy applications.